Petrogenesis, geodynamic setting, age of Rhyacian igneous rocks, from Nampala gold deposit: Implications for the crustal growth of the Birimian terrain in southern Mali - Sory I.M. Konate; Mamadou L. Bouare; Anthony T. Bolarinwa; Daniel Kwayisi; Raymond Webrah Kazapoe; Elhadji Mory Traore; N.’Tcha Daniel Kouagou N’Dah (Results in Earth Sciences)
The Nampala gold deposit is a sub-world-class deposit situated within the Birimian terrain of southern Mali, it is characterized by metasedimentary, intrusive, and graphitic schist rocks. This study investigated the petrography, geochemistry, and geochronology of the intrusive rocks (lamprophyre and granitoid) to elucidate their origins, petrogenesis, age, and tectonic settings. The lamprophyres are porphyritic and holocrystalline and are composed of pyroxene and amphibole, some of the mafic minerals have been altered to talc. The granitoids are coarse-grained and composed predominantly of plagioclase, with minor quartz, microcline, biotite, and sulfides. The lamprophyres exhibit subalkaline, specifically calc-alkaline characteristics, enrichment of Light Rare Earth Elements (LREE) to Heavy Rare Earth Elements (HREE), intermediate ratios of Dy/Yb and Sm/Yb between 1.8 – 2.0 and 2.5 – 2.9, respectively, high Rb/Sr (0.56 – 0.79), and low Ba/Rb (2.04 – 2.50) ratios. These features indicate formation through low-degree partial melting of phlogopite-bearing lherzolite in the spinel-garnet transition zone at depths of 75–80 km. The granitoids are granodiorite and crystallized at 2.1 Ga, I-type. They are peraluminous, and high-K calc-alkaline, with subchondritic εHf(t) values (-1.83–3.3) and TDM1 model ages (2.52 – 2.33 Ga). These signatures suggest a hybrid origin involving juvenile mantle melts and recycled Paleoproterozoic crust during an accretionary orogen. The Mg# and SiO2 contents of the granitoids' along with REE patterns and Ba, Sr, and Eu anomalies, imply melting of the delaminated lower crust. Trace element patterns, and negative Nb, Ta, and Ti anomalies, support a subduction-related genesis for both rock types. The findings provide critical constraints on the subduction-accretion processes contributing to the evolution of the Birimian Terrain within the West African Craton.